Aid, employment and inclusive growth in conflict-affected countries: Policy recommendations for Liberia - Graciana del Castillo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
The experience and lessons of the last two decades have shown that ignoring the key differences between the economics of peace and the economics of development has been a major reason why countries relapse into conflict. This paper briefly analyses such differences and their important implications for effective policymaking in war-torn countries, and against this background, it makes recommendations for the creation of reconstruction zones in Liberia. Reconstruction zones would have two distinct but linked areas to ensure synergies between them - an export-oriented reconstruction zone, consisting of any existing agricultural or mining foreign concession, and a local production reconstruction zone focusing on rural development, that would produce agricultural goods, food, light manufacturing and services for the domestic market, including for the concessions. The purposes of reconstruction zones are as follows. First, to create links between the concessions, operating as enclaves, and the domestic economy, particularly with the rural communities in their vicinity that have often been displaced or their livelihoods threatened by them. Second, to focus on rural development to improve food security and decrease dependence on imports. Third, to support business development through the creation of a level playing field in infrastructure and credit for micro and small enterprises, including small farmers. Fourth, to move away from the fragmented aid and investment strategies of the past, to a more integrated and effective aid strategy. Last but not least, to achieve more inclusive growth that could help to consolidate peace and avoid that Liberia relapses into conflict.
Keywords: F5; D74; Q34; Q0; Q1; Z18; O55; 330; international relations and international political economy; conflict; natural